Asia Cell Telecommunications Company Is Used as a Case Study to Examine How Advertising and Its Techniques Affect Customer Behavior Decisions. - Abbas Jasim Mohammad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: In increasingly competitive markets, advertising serves as a core communication tool for connecting companies with consumers and shaping purchasing decisions. Specific Background: This study examines advertising practices within a telecommunications context, focusing on Asia Cell as a case study to analyze how advertising content, media, repetition, and credibility relate to consumer behavior. Knowledge Gap: Despite extensive use of advertising, empirical understanding of how specific advertising components jointly relate to consumer decision-making in developing markets remains limited. Aims: This research aims to analyze the relationship between advertising elements and consumer behavior and to assess how these factors contribute to purchasing decisions among Iraqi consumers. Results: The findings reveal a statistically significant relationship between advertising and consumer behavior, with content showing the strongest association, followed by media, credibility, and repetition. Digital media, particularly social platforms, attracted the highest engagement, while repeated exposure reinforced brand recall. Credibility was also linked to post-purchase behavior and loyalty. Novelty: This study integrates multiple advertising dimensions into a unified analytical model applied to a real telecommunications case using quantitative methods. Implications: The results provide practical insights for optimizing advertising strategies, emphasizing targeted content, appropriate media selection, and balanced repetition to strengthen consumer engagement and purchasing decisions. Highlights:• Clear and creative messaging strongly associated with purchase intention• Social platforms generated highest audience engagement among channels• Trust in promotional messages linked to loyalty and post-buy actions Keywords: Advertising Content, Advertising Media, Consumer Behavior, Purchase Decision, Advertising Credibility